Productivity analysis of wheat (Triticum aestivium) in irrigated sub-tropics of Jammu - KUMAR, RAKESH; SLATHIA, P S; NAIN, M S; SHARMA, B C; GUPTA, S K; PANOTRA, NARINDER (The Indian Journal of Agricultural Sciences, 2022)
Present study was carried out in Jammu district of Jammu and Kashmir with 180 randomly selected wheat growers from three different blocks (R.S. Pura, Suchetgarh and Bishnah) with the objective to analyze the productivity status of wheat (Triticum aestivium L.) crop in irrigated sub-tropics during 2020–21. There was large variation in productivity of wheat crop in different wheat growing regions of the state. Results of the study revealed that all the farmers sown their wheat crop by broadcasting method, 36% farmers replaced their wheat seed and same percentage of farmers adopted the practice of seed treatment. All the farmers applied DAP and urea as basal dose at sowing time and herbicide for controlling narrow and broad leaved weeds. Only 45% farmers applied first irrigation at the crown root initiation stage. Second dose of urea was applied by 100% farmers after first irrigation and 60% farmers applied third dose of urea in their wheat crop. Only 18% of sampled farmers sprayed fungicides. Overall average wheat crop productivity of respondent farmers in study area was 2.789 t/ha and R. S. Pura block had significant difference in productivity of wheat crop as compared to Bishnah (P=.039) and Suchetgarh (P=.010) block.